Validation of a Patient-Reported Outcome Measure for Moist Desquamation among Breast Radiotherapy Patients - Cheryl Duzenli; Elisa K. Chan; Theodora Koulis; Sheri Grahame; Joel Singer; David Morris; Josslynn Spence; Terry Lee; Levi Burns; Robert A. Olson (Current Oncology, 2022)
There has been an increasing interest in patient-reported outcome (PRO) measures in both the clinical and research settings to improve the quality of life among patients and to identify when clinical intervention may be needed. The primary purpose of this prospective study was to validate an acute breast skin toxicity PRO measure across a broad sample of patient body types undergoing radiation therapy. Between August 2018 and September 2019, 134 women undergoing adjuvant breast radiotherapy (RT) consented to completing serial PRO measures both during and post-RT treatment and to having their skin assessed by trained trial radiation therapists. There was high patient compliance, with 124 patients (92.5%) returning to the clinic post-RT for at least one staff skin assessment. Rates of moist desquamation (MD) in the infra-mammary fold (IMF) by PRO were compared with skin assessments completed by trial radiation therapists. There was high sensitivity (86.5%) and good specificity (79.4%) between PRO and staff-reported presence of MD in the IMF, and there was a moderate correlation between the peak severity of the MD reported by PRO and assessed by staff (rho = 0.61, p < 0.001). This prospective study validates a new PRO measure to monitor the presence of MD in the IMF among women receiving breast RT.